The pain course: a randomised controlled trial comparing a remote-delivered chronic pain management program when provided in online and workbook formats. Issue 7 (July 2017) - Dear, B.F.; Gandy, M.; Karin, E.; Ricciardi, T.; Fogliati, V.J.; McDonald, S.; Staples, L.G.; Perry, K. Nicholson; Sharpe, L.; Nicholas, M.K.; Titov, N.
Abstract : Abstract: This study compared a remote-delivered pain management program, the Pain Course, when delivered in online and workbook formats. Participants (n = 178) were randomised into 2 groups: (1) an Internet Group (n = 84) who were provided with secure accounts to the program in an online format; or (2) a Workbook Group (n = 94) who were mailed workbook versions of the program. The content of both programs was identical and comprised 5 core lessons, which participants were encouraged to work through over an 8-week period, according to a prescribed timetable. All participants were provided with weekly contact with a clinical psychologist through email and telephone throughout the program. The overall findings suggest that the workbook format was no less effective or acceptable than the validated online format. Significant improvements (avg. improvement; Internet Group vs Workbook Group) in levels of disability (PDI: 16% vs 24%; RMDQ: 12% vs 15%), anxiety (GAD-7: 36% vs 26%), and depression (PHQ-9: 36% vs 36%) were observed in both groups immediately posttreatment. Further improvements were observed in disability levels to 3-month follow-up, and improvements across the other primary outcomes were maintained until 12-month follow-up. High treatment completion rates and levels of satisfaction were reported in both groups, and both groups required a similarly small amount of clinician contact per participant (M = 74.85 minutes; SD = 41.03). These results highlight the public health potential of remote-delivered pain management programs, delivered in either workbook or online formats, as methods of increasing access to pain management. Abstract : Online and workbook versions of a remote-delivered pain management program were examined. Clinically meaningful improvements were observed with no marked differences between versions.